Determinants of neonatal near-miss among neonates delivered in public hospitals of Ilu Abba Bor Zone, Southwest Ethiopia: An unmatched case–control study during the COVID-19 pandemic - Debele, Gebiso Roba; Siraj, Sabit Zenu; Tsegaye, Dereje; Temesgen, Ermiyas (Frontiers in Public Health, 2022)
Background: Due to COVID-19 outbreak, diverted resources from routine maternal health services, declines access to routine pediatric care which increases the of Neonatal Near Miss (NNM). It has been hypothesized that identifying the determinant of NNM during this outbreak is very important for taking timely interventions that could enhance the quality of newborn care through which neonatal mortality could be reduced. However, there were few studies done on determinants of neonatal near miss in Ethiopia specifically in the study area. Thus, this study identified determinants of NNM among neonates admitted in public hospitals of Ilu Abba Bor Zone South West Ethiopia, 2020. Methods: An institution based unmatched case-control study was conducted among randomly selected 303 (101 cases and 202 controls) neonates admitted to Mettu Karl Comprehensive Specialized Hospital (MKSH) and Darimu Primary Hospital (DPH) from November 1 to 28, 2020. The data was entered onto Epi-Data version 4.6, then exported to SPSS version 20 for analysis. A P values < 0.05 was considered to declare the statistical significance in the multivariable analysis in this study. Result: A total of 303(101 cases and 202 controls) neonates admitted to MKSH and DPH were included to the study making 98% response rate. In multivariable logistic regression analysis, no formal maternal education [AOR=3.534, 95% CI: (1.194-10.455)], Breech presentation during birth [AOR=3.088, 95% CI: (1.029-9.268)], less than 4 Ante Natal Care (ANC) visits [AOR=1.920, 95% CI: (1.065-3.461], Caesarean section delivery [AOR= 4.347, 95% CI: (1.718-10.996)], antepartum hemorrhage (APH) [AOR= 3.37, 95% CI: (1.23-9.24)] and Hypertensive Disorder of Pregnancy (HDP) [AOR= 4.05, 95% CI: (2.36-11.05)], were independent determinants of NNM. Conclusion: The finding of the study showed that, educational level, presentation during birth, ANC visit and mode of delivery, APH and HDP were remains a significant determinant of the NNM during this pandemic in resource limited setting specifically Ethiopia. Therefore, much work is needed to improve neonatal health by providing adequate ANC services and other identified potential determinant factors that predispose the newborn for life-threatening (near-miss) conditions especially in during this pandemic.